Clinical and epidemiological aspects of American cutaneous leishmaniasis with genital involvement, - Marcelo Rosandiski Lyra; Alan Bittencourt da Silva; Cláudia Maria Valete-Rosalino; Maria Inês Fernandes Pimentel (Sociedade Brasileira de Dermatologia, 2020)
Abstract Genital lesions are an unusual presentation of American cutaneous leishmaniasis. Conditions such as disseminated cutaneous leishmaniasis and HIV infection may be associated with genital involvement. The authors present five cases of American cutaneous leishmaniasis with genital lesions and discuss the clinical and epidemiological aspects observed in this case series.